Integrating self-management support for knee injuries into routine clinical practice: TRAK intervention design and delivery. (February 2018) - Button, Kate; Nicholas, Kevin; Busse, Monica; Collins, Mark; Spasić, Irena
Abstract: Background: TRAK is a web-based intervention that provides knee patients with health information, personalised exercise plans and remote clinical support. The aim of this study was to fully define TRAK intervention content, setting and context and develop the training through an implementation study in a physiotherapy out-patient service. Methods: A mixed methods study.Phase 1 was a qualitative interview study, whereby fifteen physiotherapists used TRAK for 1 month with a patient of their choice. Interviews explored patient and physiotherapist views of TRAK intervention and training requirements. InPhase 2 seventy-four patients were recruited, all received conventional physiotherapy, a subset of 48 patients used TRAK in addition to conventional Physiotherapy. Aspects of feasibility measured included: uptake and usage of TRAK . Results: Patients and physiotherapists reported that TRAK was easy to use and highlighted the therapeutic benefit of the exercise videos and personalised exercise plans to remind them of their exercises and the correct technique. Patients reported needing to use TRAK with the guidance of their treating physiotherapist initially. Physiotherapists highlighted appointment time constraints and lack of familiarity with TRAK as factors limiting engagement. In Phase 2, 67% patients accessed TRAK outside of the clinical environment. A total of 91% of patients were given a personalised exercise plan, but these were only updated in 34% of cases. Conclusion: A comprehensive training package for patients and clinicians has been defined. The refined TRAK intervention is reported using the 'Template for Intervention Description and Replication in preparation for a definitive randomised control trial. Highlights: Fully defined TRAK web-based supported self-management intervention for knee rehabilitation. Training package for TRAK intervention identified. Findings mapped to behaviour change wheel to explore underlying mechanisms for TRAK success.